O sabor do território: o design estratégico e a valorização do arroz do litoral norte gaúcho e do doce de Pelotas - Oliveira, Ágata Morena de Britto (Universidade do Vale do Rio dos Sinos, 2013)
Eating a local product doesn't just mean to consume close to home items/products, something from the surrounding areas, but also to acquire a number of symbols and significances that are closely connected to a territory, to a certain culture and/or to a group of people. The local product is intimately related to the landscape of its territory, its natural resources, the people that inhabits there and its traditions. However, many times all these values are lost in the path from the producer to the consumer of such product. There are various possible explanations to justify the lack of value given to local products. In this project it will be discussed the need of changing this exchange operation logic between its several agents. The research made to develop this study shows the dominance of the economic field and its values in these operations. Because of that the perception of its significance and what food represents is put aside. But there is something fundamental that is being left behind: the fact that we eat in a certain way because of all the factors and significant things we had during our lives. Therefore, eating is a cultural act. Thus, having a look at the exchange operations of local products within its cultural field values may bestow new possibilities for the agents that are part of this chain. The proposal of this dissertation is to reflect upon the discontinuity of the current logic. To be able to conceive it it is necessary to project a system that blends into this new aspects of the exchange interrelation. Intending to understand the local product exchange operation dynamics it was chosen as the object of this study products that have origin certification. With the perspective of a new logic, the strategic design can operate on projecting these systems and new ways for the agents to interact and negotiate the local products; because it can establish connections between the significance and materiality within the systems. In a complex universe it is needed to establish a systemic emphasis when trying to solve the current problems. And this systemic logic supports the search for a sustainable development. To make this body a operation strategy within the Service-Product System favours the agents consciousness and, at the same time, there is a double benefit - to the environment and to the community and also to the product. To promote these directed changes in the local system, i.e., to stimulate, to participate and to make it easy to break the dominant "way-to-do-it" is a strength the design can take up by the means of its insertion in the systems of the study objects.
Keywords: Cultura; Design estratégico; Comida; Território; Produto local; Culture; Strategic design; Food; Local product; Territory; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial